1946
DOI: 10.1086/281373
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Heterosis. I. Metabolic Capacity of Different Races of Drosophila melanogaster for Egg Production

Abstract: striking utilization of this fact has come in corn breeding, where the hybrid is often able to fix food materials in excess of 2 or 3 times that of the inbred parents. But the observation is not limited in any way to corn. It is true in most instances for small grains, vegetables, fruits, flowers, economic animals, domestic birds and man.Universal as this phenomenon is, exceptions do occur.These exceptions are as interesting as the occurrences, for they serve to demonstrate that there is much behind hybridity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1952
1952
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…A complete lack of hatching occurs when females are 40 or 50 days old. Such curves are typical of that which has been known for a long time in Drosophila (Hadorn and Zeller, 1943;David and Croissant, 1956;Gowen and Johnson, 1946;Perrin-Valdemer, 1966;Fowler, 1973). Decrease in egg hatching reflects an alteration of the reproductive capacity of both females and males as a consequence of senescence (David et al, 1975).…”
Section: ) Egg Hatchability or Fertilitysupporting
confidence: 56%
“…A complete lack of hatching occurs when females are 40 or 50 days old. Such curves are typical of that which has been known for a long time in Drosophila (Hadorn and Zeller, 1943;David and Croissant, 1956;Gowen and Johnson, 1946;Perrin-Valdemer, 1966;Fowler, 1973). Decrease in egg hatching reflects an alteration of the reproductive capacity of both females and males as a consequence of senescence (David et al, 1975).…”
Section: ) Egg Hatchability or Fertilitysupporting
confidence: 56%
“…This phenomenon of increased egg production following hybridization has been well demonstrated in D. melanogaster by Gowen and Johnson (1946), who pointed out that hybrids between inbred strains start production at high levels but cannot maintain a lesser rate of loss than the inbred strains. Such is the situation with these chromosomal heterozygotes: after an initially rapid egg production the rate of loss is greater than in the homozygotes so that all types produce at the same rate in senesence.…”
Section: Discussionmentioning
confidence: 70%
“…An associated selection experiment (Rose and Charlesworth, 1981b) is difficult to interpret, but provides some indirect evidence ofa negative response of longevity to selection for increased fecundity. Gowen and Johnson (1946) also found a negative correlation between survival and fecundity, but Temin (1966), Giesel (1979) and Simmons et al (1980) all found that survival and fecundity were positively correlated. Rose and Charlesworth (198la) point out that these latter studies used new mutations (Simmons et al, 1980) or highly inbred lines (Giesel), or else involved complete sterility (Temin).…”
Section: The Cost Hypothesismentioning
confidence: 96%